2013
DOI: 10.1002/app.39671
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of capsanthin by soybean protein isolate‐chitosan coacervation and microcapsule stability evaluation

Abstract: Although capsanthin possesses excellent coloring performance and healthcare functions, its application in the food industry is limited due to its susceptibility to humidity, heat, and light. The purpose of this research was to microencapsulate capsanthin by soybean protein isolate (SPI)-chitosan coacervation and evaluate whether the microencapsulation improved the stability of capsanthin against the adverse conditions mentioned above. The results indicated that the optimum conditions for capsanthin microencaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Chitosan led to a noticeable improvement of the polymeric membrane barrier, reducing water vapor and oxygen diffusion while reducing light penetration. However, the hygroscopicity of proteins may be a restrictive factor for stabilizing carotenoids, particularly at high RH (Qv et al, 2011;Xiao et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations
“…Chitosan led to a noticeable improvement of the polymeric membrane barrier, reducing water vapor and oxygen diffusion while reducing light penetration. However, the hygroscopicity of proteins may be a restrictive factor for stabilizing carotenoids, particularly at high RH (Qv et al, 2011;Xiao et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Plant proteins have also been used successfully to develop complex coarcervates for encapsulating carotenoids (Xiao et al, 2014). Using chitosan and soy protein isolate to form coacervates containing capsanthin, it was shown that the emulsification conditions (homogenization speed, temperature), the core:wall ratio and wall material concentrations influence microencapsulation yield and efficiency, as well as the microparticulate morphological characteristics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, various studies on xanthophyll stability formulations that could lead to potential bioavailability enhancer products. One of them comprises formulations in microcapsules obtained by complex coacervation [74] and supramolecular complexes [75]; where xanthophyll oxidative, humidity, heat and light stability have been achieved.…”
Section: Future Trends In the Purification And Formulation Of Xanthopmentioning
confidence: 99%
“…Blends of chitosan and soy protein have been investigated for applications, such as drug delivery systems [12], wound dressings and tissue regeneration [13][14][15][16][17], edible films and conjugates, and microencapsulation of food ingredients [18][19][20][21][22]. In these applications, the blends were prepared by using separate solvents for each of the polymers.…”
Section: Introductionmentioning
confidence: 99%